Determination STEM (mathematics) blended learning criteria via fuzzy AHP method - Durrani Aimi, Abdul Malik; Yuhani, Yusof; Ku Muhammad Naim, Ku Khalif (AIP Publishing, 2024)
Due to the decreasing number of students’ interest in the Science, Technology, Engineering, and Mathematics (STEM) field in Malaysia, educators need to instill students of STEM education in teaching and learning to face the IR 4.0 revolution. However, due to the COVID-19 pandemic and the recent curriculum change may challenge educators in implementing STEM (Mathematics). Thus, blended learning is relevant in maintaining the maximum students' higher thinking skills by integrating the STEM-Mathematics criteria in teaching and learning. Proper selection of STEM (Mathematics) criteria can ensure high-impact achievement and the fulfilment of the Ministry of Education's aspirations. This study proposes the STEM criteria needed in Mathematics subjects via the fuzzy Analytic Hierarchy Process (AHP) method. This study aims to evaluate the STEM (Mathematics) criteria weight for identifying the appropriate STEM (Mathematics) criteria needed in blended learning. First, the potential of STEM (Mathematics) criteria and the standard curriculum for secondary school were identified by the literature review and evaluated by distributing questionnaires to 31 expert mathematics educators. Then, fuzzy AHP is utilised to illustrate the proposed approach. The results depicted the ranking order of the STEM (Mathematics) criteria using linguistic scales.